(untitled) (Педагогіка вищої та середньої школи, 2004)
The article deals with the attempts of the author to сlassify the laws and regulations of the development of the national educational and upbringing systems of the Ukrainian фтвneighbouring peoples who for a long time lived under the сonditions of absence of state.